Suggestioni rimbaudiane nell’opera di Elsa Morante: un’ipotesi di lettura - Rubinacci, Antonella (Italogramma, 2021)
<span dir="ltr" style="left: calc(var(--scale-factor)*56.64px); top: calc(var(--scale-factor)*234.91px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.902758);" role="presentation">The <span dir="ltr" style="left: calc(var(--scale-factor)*78.74px); top: calc(var(--scale-factor)*234.91px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.86558);" role="presentation">paper <span dir="ltr" style="left: calc(var(--scale-factor)*108.74px); top: calc(var(--scale-factor)*234.91px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.921928);" role="presentation">intends to analyse the influence of Arthur Rimbaud's works on Elsa Morante's texts and, <span dir="ltr" style="left: calc(var(--scale-factor)*56.64px); top: calc(var(--scale-factor)*248.71px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.972073);" role="presentation">specifically, on <span dir="ltr" style="left: calc(var(--scale-factor)*136.46px); top: calc(var(--scale-factor)*248.71px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.972741);" role="presentation">Il mondo salvato dai ragazzini<span dir="ltr" style="left: calc(var(--scale-factor)*290.33px); top: calc(var(--scale-factor)*248.71px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.974653);" role="presentation">, a book published in 1968 that stands out for its <span dir="ltr" style="left: calc(var(--scale-factor)*56.64px); top: calc(var(--scale-factor)*262.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.897901);" role="presentation">remarkable <span dir="ltr" style="left: calc(var(--scale-factor)*119.74px); top: calc(var(--scale-factor)*262.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.910103);" role="presentation">heterogeneity, <span dir="ltr" style="left: calc(var(--scale-factor)*197.34px); top: calc(var(--scale-factor)*262.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00065);" role="presentation">multiformity <span dir="ltr" style="left: calc(var(--scale-factor)*267.85px); top: calc(var(--scale-factor)*262.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.863568);" role="presentation">and <span dir="ltr" style="left: calc(var(--scale-factor)*294.36px); top: calc(var(--scale-factor)*262.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.963735);" role="presentation">complexity. <span dir="ltr" style="left: calc(var(--scale-factor)*360.56px); top: calc(var(--scale-factor)*262.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.919594);" role="presentation">Starting <span dir="ltr" style="left: calc(var(--scale-factor)*407.69px); top: calc(var(--scale-factor)*262.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.969);" role="presentation">from <span dir="ltr" style="left: calc(var(--scale-factor)*440.20px); top: calc(var(--scale-factor)*262.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the <span dir="ltr" style="left: calc(var(--scale-factor)*464.06px); top: calc(var(--scale-factor)*262.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.895952);" role="presentation">reading <span dir="ltr" style="left: calc(var(--scale-factor)*509.17px); top: calc(var(--scale-factor)*262.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.895868);" role="presentation">marks <span dir="ltr" style="left: calc(var(--scale-factor)*56.64px); top: calc(var(--scale-factor)*276.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912775);" role="presentation">(annotations, underlinings, reminders<span dir="ltr" style="left: calc(var(--scale-factor)*236.09px); top: calc(var(--scale-factor)*276.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.939047);" role="presentation">) found <span dir="ltr" style="left: calc(var(--scale-factor)*274.25px); top: calc(var(--scale-factor)*276.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.952045);" role="presentation">in the writer’s <span dir="ltr" style="left: calc(var(--scale-factor)*344.95px); top: calc(var(--scale-factor)*276.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.918344);" role="presentation">volumes of the <span dir="ltr" style="left: calc(var(--scale-factor)*419.83px); top: calc(var(--scale-factor)*276.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.87843);" role="presentation">Oeuvres (<span dir="ltr" style="left: calc(var(--scale-factor)*466.78px); top: calc(var(--scale-factor)*276.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.912579);" role="presentation">now availables <span dir="ltr" style="left: calc(var(--scale-factor)*56.64px); top: calc(var(--scale-factor)*290.11px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.928875);" role="presentation">for consultation)<span dir="ltr" style="left: calc(var(--scale-factor)*136.22px); top: calc(var(--scale-factor)*290.11px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.900074);" role="presentation">, the aim is therefore to reconstruct the traces of a dialogue that is not only based on <span dir="ltr" style="left: calc(var(--scale-factor)*56.64px); top: calc(var(--scale-factor)*303.91px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.959656);" role="presentation">some extracts of verses or intertextual references, but also on <span dir="ltr" style="left: calc(var(--scale-factor)*377.11px); top: calc(var(--scale-factor)*303.91px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.891232);" role="presentation">shared experiences <span dir="ltr" style="left: calc(var(--scale-factor)*475.90px); top: calc(var(--scale-factor)*303.91px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.924041);" role="presentation">(ecstatic and <span dir="ltr" style="left: calc(var(--scale-factor)*56.64px); top: calc(var(--scale-factor)*317.71px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.948367);" role="presentation">hallucinatory journeys), <span dir="ltr" style="left: calc(var(--scale-factor)*179.42px); top: calc(var(--scale-factor)*317.71px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.896277);" role="presentation">models <span dir="ltr" style="left: calc(var(--scale-factor)*219.65px); top: calc(var(--scale-factor)*317.71px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.90895);" role="presentation">(Baudelaire, <span dir="ltr" style="left: calc(var(--scale-factor)*284.09px); top: calc(var(--scale-factor)*317.71px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.939542);" role="presentation">Nerval, <span dir="ltr" style="left: calc(var(--scale-factor)*325.39px); top: calc(var(--scale-factor)*317.71px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.949802);" role="presentation">Michelet, <span dir="ltr" style="left: calc(var(--scale-factor)*376.51px); top: calc(var(--scale-factor)*317.71px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.879664);" role="presentation">the t<span dir="ltr" style="left: calc(var(--scale-factor)*400.03px); top: calc(var(--scale-factor)*317.71px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.999005);" role="presentation">exts of oriental spirituality) <span dir="ltr" style="left: calc(var(--scale-factor)*56.64px); top: calc(var(--scale-factor)*331.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.891724);" role="presentation">languages and theoretical conceptions. <span dir="ltr" style="left: calc(var(--scale-factor)*245.45px); top: calc(var(--scale-factor)*331.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.886613);" role="presentation">The paper <span dir="ltr" style="left: calc(var(--scale-factor)*297.17px); top: calc(var(--scale-factor)*331.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.927126);" role="presentation">will then observe<span dir="ltr" style="left: calc(var(--scale-factor)*379.99px); top: calc(var(--scale-factor)*331.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925427);" role="presentation">, always by making <span dir="ltr" style="left: calc(var(--scale-factor)*476.98px); top: calc(var(--scale-factor)*331.51px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.88016);" role="presentation">references to <span dir="ltr" style="left: calc(var(--scale-factor)*56.64px); top: calc(var(--scale-factor)*345.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.915599);" role="presentation">Rimbaud, <span dir="ltr" style="left: calc(var(--scale-factor)*107.78px); top: calc(var(--scale-factor)*345.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.938846);" role="presentation">how <span dir="ltr" style="left: calc(var(--scale-factor)*132.50px); top: calc(var(--scale-factor)*345.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.116);" role="presentation">it <span dir="ltr" style="left: calc(var(--scale-factor)*143.30px); top: calc(var(--scale-factor)*345.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.938405);" role="presentation">can actually b<span dir="ltr" style="left: calc(var(--scale-factor)*212.21px); top: calc(var(--scale-factor)*345.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.901888);" role="presentation">e possible <span dir="ltr" style="left: calc(var(--scale-factor)*265.01px); top: calc(var(--scale-factor)*345.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.925316);" role="presentation">to trace a path <span dir="ltr" style="left: calc(var(--scale-factor)*340.15px); top: calc(var(--scale-factor)*345.31px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.970595);" role="presentation">in Morante's vision of art and its role in <span dir="ltr" style="left: calc(var(--scale-factor)*56.64px); top: calc(var(--scale-factor)*359.11px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(1.00792);" role="presentation">reality fr<span dir="ltr" style="left: calc(var(--scale-factor)*99.62px); top: calc(var(--scale-factor)*359.11px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.94149);" role="presentation">om the book under examination – <span dir="ltr" style="left: calc(var(--scale-factor)*272.81px); top: calc(var(--scale-factor)*359.11px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.963022);" role="presentation">Il mondo salvato dai ragazzini – <span dir="ltr" style="left: calc(var(--scale-factor)*440.02px); top: calc(var(--scale-factor)*359.11px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.9336);" role="presentation">to <span dir="ltr" style="left: calc(var(--scale-factor)*453.70px); top: calc(var(--scale-factor)*359.11px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.951142);" role="presentation">Aracoeli<span dir="ltr" style="left: calc(var(--scale-factor)*494.98px); top: calc(var(--scale-factor)*359.11px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.951391);" role="presentation">, her last <span dir="ltr" style="left: calc(var(--scale-factor)*56.64px); top: calc(var(--scale-factor)*372.91px); font-size: calc(var(--scale-factor)*12.00px); font-family: sans-serif; transform: scaleX(0.920763);" role="presentation">apocalyptic novel.